1993
DOI: 10.1007/bf00186625
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical hypothyroidism: neurobehavioral features and beneficial effect of l-thyroxine treatment

Abstract: Frank hypothyroidism is known to induce neurological and mental dysfunction. The aim of this study was to assess selected neuropsychological and behavioral features by means of standardized tests in a group of 14 patients with subclinical hypothyroidism who were free from neuropsychological complaints and to evaluate the possible effects of L-thyroxine treatment on their performance. Patients were submitted to the Crown and Crisp Experiential Index and to the Wechsler Memory Scale; their ratings on the neurobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
135
1
15

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(160 citation statements)
references
References 21 publications
(20 reference statements)
9
135
1
15
Order By: Relevance
“…Third, certain neurobehavioral and neuromuscular dysfunctions are also associated with hypothyroidism, e.g. depression, memory loss, cognitive impairment and peripheral nerve dysfunction [28][29][30]. The prevalence of depression in dialysis patients is high [31], and hypothyroidism can contribute to its development.…”
Section: Discussionmentioning
confidence: 99%
“…Third, certain neurobehavioral and neuromuscular dysfunctions are also associated with hypothyroidism, e.g. depression, memory loss, cognitive impairment and peripheral nerve dysfunction [28][29][30]. The prevalence of depression in dialysis patients is high [31], and hypothyroidism can contribute to its development.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is still controversial whether subclinical hypothyroidism is associated with depression or cognitive dysfunction [24,25], it seems possible that disability and/or depressed mood due to endocrinological dysfunction could decrease the physical activity of daily life, which may result in the reduction of mechanical load on heel. On the contrary, loss of physical activity and hypothyroidism might increase body weight, which would be positively associated with bone mass, though there was no association between BMI and heel QUS in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The data in the literature concerning this topic are inconsistent and only published for chronic hypothyroidism in non-DTC patients, which is not necessarily comparable with short-term hypothyroidism after 4 weeks of levothyroxine withdrawal in DTC patients. In a consecutive sample, Monzani et al (29) found increased anxiety in subclinical hypothyroid patients. The authors claimed that the cause of higher anxiety scores in subclinical hypothyroid subjects might be minor neurobehavioral disturbances.…”
Section: Dtc-h (%)mentioning
confidence: 96%